2006
DOI: 10.1242/dev.02696
|View full text |Cite
|
Sign up to set email alerts
|

LDL-receptor-related protein 4 is crucial for formation of the neuromuscular junction

Abstract: Low-density lipoprotein receptor-related protein 4 (Lrp4) is a member of a family of structurally related, single-pass transmembrane proteins that carry out a variety of functions in development and physiology, including signal transduction and receptor-mediated endocytosis. Lrp4 is expressed in multiple tissues in the mouse, and is important for the proper development and morphogenesis of limbs, ectodermal organs, lungs and kidneys. We show that Lrp4 is also expressed in the post-synaptic endplate region of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
370
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(386 citation statements)
references
References 68 publications
10
370
0
6
Order By: Relevance
“…1C). When crossed with a ubiquitous Cre driver line P Bi-2 -cre (32), the resulting constitutive Lrp4-deficient mice died perinatally, recapitulating the previously reported phenotype of Lrp4-null mice (17). Upon closer inspection, Lrp4 flox/flox ;P Bi-2 -cre animals exhibited polysyndactyly (Fig.…”
Section: Lrp4 Deletion In Osteoblasts/osteocytes Results In Increasedsupporting
confidence: 77%
See 2 more Smart Citations
“…1C). When crossed with a ubiquitous Cre driver line P Bi-2 -cre (32), the resulting constitutive Lrp4-deficient mice died perinatally, recapitulating the previously reported phenotype of Lrp4-null mice (17). Upon closer inspection, Lrp4 flox/flox ;P Bi-2 -cre animals exhibited polysyndactyly (Fig.…”
Section: Lrp4 Deletion In Osteoblasts/osteocytes Results In Increasedsupporting
confidence: 77%
“…LRP4 has a well-recognized role in its interplay with agrin and muscle-specific kinase (MuSK) in the formation and stabilization of the neuromuscular junction (NMJ) (17)(18)(19), a synaptic connection that is required for communication between motor neurons and muscle fibers. Accordingly, Lrp4 loss-of-function results in perinatal lethality in mice due to breathing failure (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LRP4 levels influence the shape of dendritic arbors prior to affecting the density of dendritic spines Previous studies demonstrated that in Lrp4 −/− mice the α-motoneuron growth cone continues to grow along the muscle fiber and fails to develop into a presynaptic terminal (Weatherbee et al, 2006). As a consequence, axons with deficient capacity to establish synapses might become unusually long.…”
Section: Resultsmentioning
confidence: 99%
“…A key regulator for NMJ development is the low-density lipoprotein receptor-related protein 4 (LRP4; Weatherbee et al, 2006;Wu et al, 2012;Yumoto et al, 2012). At the NMJ, LRP4 forms a complex with the muscle-specific tyrosine kinase MuSK in the muscle fiber plasma membrane; this complex serves as the receptor for the motoneuron-derived extracellular matrix protein agrin (Kim et al, 2008;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%